A hybrid traffic scheduling mechanism applied to large scale time-sensitive networking - Yanjue LI; Wenxuan HAN; Hailong ZHU; Changchuan YIN (物联网学报)
Aiming at large-scale time-sensitive networking (TSN) scenarios that can only ensure frequency synchronization between devices, a hybrid traffic scheduling mechanism was proposed based on time-aware shaper (TAS) combined with cycle specified queuing and forwarding (CSQF).Firstly, a scheme was investigated for achieving periodic cyclic mapping alignment between two adjacent nodes located in different time domains.Secondly, combining segment routing technology, a heuristic algorithm based on CSQF mechanism for joint routing and scheduling was proposed to complete resource allocation for large bandwidth traffic.The experimental results show that the proposed scheme significantly improves the system resource utilization and scheduling success rate compared to existing research results, achieving efficient TSN traffic scheduling in wide area network scenarios.